Oxygen nonstoichiometry, defect equilibria, and thermodynamic characterization of LaMnO3 perovskites with Ca/Sr A-site and Al B-site doping. (15th January 2016) - Takacs, M.; Hoes, M.; Caduff, M.; Cooper, T.; Scheffe, J.R.; Steinfeld, A.
Abstract: This work encompasses the thermodynamic characterization of four doped lanthanum manganites, namely La0.6 A 0.4 Mn1−y Aly O3 ( A = Ca, Sr and y = 0, 0.4), all showed to be promising redox materials for the solar thermochemical splitting of H2 O and CO2 to H2 and CO. We present oxygen nonstoichiometry measurements in the temperature range T = 1573 K–1773 K and oxygen partial pressure range p O2 = 4.5066 × 10 −2 bar–9.9 × 10 −5 bar. For a given T and p O2, oxygen nonstoichiometry is found to be higher when replacing the divalent dopant Sr in La0.6 Sr0.4 MnO3 by the divalent Ca but also increases significantly when additionally doping 40 mol-% Al to the Mn-site. La0.6 Ca0.4 Mn0.6 Al0.4 O3 revealed the highest mass specific oxygen release, 0.290 mol O2 per kg metal oxide at T = 1773 K and p O2 = 2.360 × 10 −3 bar and 0.039 mol kg −1 at T = 1573 K and p O2 = 4.5066 × 10 −2 bar. It is shown that the chemical defect equilibrium of all four perovskites can be accurately described by the two simultaneous redox couples Mn 4+ /Mn 3+ and Mn 3+ /Mn 2+ . Thermodynamic properties, namely partial molar enthalpy, entropy and Gibbs free energy are consequently extracted from the defect models. Partial molar enthalpy decreases with increasing oxygen nonstoichiometry for the Al-doped perovskites whereas the opposite trend is observed for the others. The enthalpy falls within the range 260–300 kJ mol −1 for all the materials. Equilibrium hydrogen yields upon oxidation with H2 O are determined as a function of redox conditions. Although reduction extents of the perovskites are greater compared to CeO2, oxidation with H2 O and CO2 is thermodynamically less favorable. This leads to lower mass specific fuel productivity compared to CeO2 under most conditions relevant for solar thermochemical cycles. Graphical abstract: